Continuing Professional Development - Preparing for New Roles in Libraries. A Voyage of Discovery. Sixth World Conference on Continuing Professional Development and Workplace Learning for the Library and Information Professions - Genoni, Paul (IFLA Publications, 2005)
Librarians and information workers the world over are faced with the constant challenge of remaining abreast of developments in their field. Rapid changes in technology and workplace roles threaten to make their skills obsolete unless they undertake constant professional development. This international collection presents a comprehensive overview of current continuing professional development theory and practice for those who manage and work in library and information services. Papers by academics and practitioners describe numerous innovative responses to emerging continuing education and training needs, including workplace learning; individual learning and learning organisations.; ""Das Buch [...] dokumentiert die Vielfalt der Fragestellungen und L